Gender and healthy eating attitude strongly predict sustainable food literacy among Turkish young adults, while Mediterranean diet adherence shows only weak correlation - Helvacı, Gizem; Tayhan, Fatma; Özbey Yücel, Ümüş (Frontiers in Public Health, 2025)
BackgroundSustainability is the main concept shaping Turkey’s development plans. Adherence to healthy and sustainable diets can significantly contribute to development goals. Based on the sustainability agenda, we aimed to determine the level of sustainable food literacy among adults. We also evaluated the effect of Mediterranean diet adherence and healthy eating attitude on sustainable food literacy.MethodsA survey form containing scales for sustainable food literacy (SFLS), adherence to the Mediterranean diet (MEDAS), and attitudes toward healthy eating (ASHN) was administered to 319 Turkish adults aged 19–40.Results40% of individuals have a low SFLS score, while 55% have a low MEDAS score. Gender affects SFLS scores, with men scoring lower (β = −0.31, p < 0.001). ASHN scores positively affect SFLS scores (β = 0.51, p < 0.001). Individuals’ SFLS scores are weakly positively correlated with MEDAS scores (r = 0.14, p = 0.013).ConclusionFemale gender and positive nutritional attitudes are major predictors of sustainable food literacy. Educational programs should be instituted to redefine gender roles, promote male engagement in environmental sustainability through the equitable distribution of domestic tasks, and positively influence individuals’ attitudes toward healthy eating. The observation that persons possessing high sustainable food literacy do not completely conform to the Mediterranean diet underscores the necessity to identify and address the issues beyond knowledge that hinder adherence to this dietary regimen through policy interventions.